Perlindungan Konsumen Terhadap Produk Pangan Berkemasan Plastik Yang Mengandung Bisphenol-A (BPA) - Metekohy, Hervian Glen Sandro; Tjoanda, Merry; Sopamena, Ronald Fadly (Faculty of Law, Universitas Pattimura, 2024)
Introduction: Consumer rights, namely consumer comfort, security and safety are absolute and non-negotiable, including in consuming food products packaged in plastic.Purposes of the Research: This study aims to analyze consumer protection for plastic-packaged food products containing Bisphenol A (BPA).Methods of the Research: The type of legal research used to examine this issue is normative juridical, where this research is based on what is written in the laws and regulations. This research method is based on primary and secondary legal materials and uses a statute approach and a conceptual approach.Results of the Research: The Due Care principle can be used as a benchmark if it is related to the problem of food product packaging containing BPA. This is because the interests of consumers are vulnerable to being misused by business actors who only pursue large profits and because business actors are in a profitable position, business actors have an obligation to pay attention to ensure that consumer interests are not misused. Consumers are always in a vulnerable position if there are business actors who ignore consumer rights. The use of BPA in plastic packaging for food products that does not comply with the provisions is clearly an illegal act. Preventive consumer protection can be carried out by the government through a number of regulations governing provisions regarding food product packaging. Repressive protection can be provided by the government by imposing strict sanctions on business actors who produce food products in plastic packaging containing BPA